Sword of the spirit, shield of faith : religion in American war and diplomacy - Preston, Andrew, 1973- (New York : Anchor Books, 2012)
This is a story of how religion has influenced American foreign relations, told through the stories of the men and women, from presidents to preachers, who have plotted the country's course in the world. Ever since John Winthrop argued that the Puritans' new home would be "a city upon a hill," Americans' role in the world has been shaped by their belief that God has something special in mind for them. But this is a story that historians have mostly ignored. In this work on the subject, the author explores the major strains of religious fervor, liberal and conservative, pacifist and militant, internationalist and isolationist, that framed American thinking on international issues from the earliest colonial wars to the twenty-first century, and he arrives at some startling conclusions.
In the Beginning. Defenders of the faith ; God is an excellent man of war ; Wars of permanent reformation. -- The American Revelation. The harmony of the world confounded ; Liberation theology. -- Imperial Destinies. Absolutist apostasies ; The benevolent empire, at home and abroad ; Manifest Destiny and its discontents. -- America's Mission. Abraham Lincoln and the first war of humanitarian intervention ; Missionaries and the imperialism of human rights ; An also chosen people ; Cuba, the Philippines, and the First Crusade. -- Woodrow Wilson and the Second Crusade. The idealistic synthesis ; Onward Christian soldiers ; The Wilsonian creed. -- Franklin Roosevelt and the Third Crusade. Princes of peace and prophets of realism ; The simple faith of Franklin Roosevelt ; The Holocaust and the moral meaning of the war ; Spiritual diplomacy ; The church unmilitant ; John Foster Dulles and the quest for a just and durable peace -- The Cold War and the Fourth Crusade. The faith of Harry Truman and the theology of George Kennan ; High priests of the Cold War : Eisenhower and the second coming of Dulles ; The great schism and the myth of consensus. -- Reformation and counterreformation. The revolutionary church in a revolutionary age ; The valley of the shadow of death ; Get thee behind me, Satan ; A Judeo-Christian foreign policy ; Ronald the Lionheart -- The last crusade?
Hardcover edition published by Knopf, 2012.
Includes bibliographical references and index.
Keywords: United States -- Foreign relations; United States -- Foreign relations -- Religious aspects; Religion and international relations -- United States -- History; Religion and politics -- United States -- History; United States -- Military policy -- Religious aspects; United States -- History, Military -- Religious aspects